Napoleon Hill's First Editions - Hill, Napoleon (Ascent Audio, 2020)
The Best of Napoleon Hill's Early Works with Commentary from Entrepreneur Media for Today's Modern World Entrepreneur Media presents the best of Napoleon's early works enhanced by the voices and hard-earned insights of today's modern entrepreneurs, small business owners, and thought leaders. These two well-known and sought-out brands have decades of how-to, self-help knowledge to bridge the gap between generations of entrepreneurs to teach them how to master their personal and professional success as they run, start, and grow their enterprises.